A rapid access to aliphatic sulfonyl fluorides - Ruting Xu (Nature Portfolio, 2019)
Sulfonyl fluorides are important probes in chemical biology and molecular pharmacology. Here, the authors report a mild visible light-mediated decarboxylative fluorosulfonylethylation for the synthesis of aliphatic sulfonyl fluorides from a wide range of carboxylic acids, including natural products and drug derivatives.